Enterpreneship Transformation in the Context of the Digitization of Business Processes - Verbivska, Liudmyla; Verbivska, Liudmyla (Postmodern Openings, 2022)
This articleexamines the transformation of enterprises activity in terms of digitalization of business processes. The rapid and global penetration of technology into business and national economies contributes to the creation of an information civilization and leads to the transformation of economic activity. Globalization and digitalization of the economy transform the key characteristics and objectives of enterprises, the directions of their development and business management processes. Technological innovations create benefits that affect the economic system as a whole and its individual components. In the new conditions of information economy development, the competitive struggle of enterprises is intensifying, the models of enterprise management are changing, and the level of digitalization of business processes is growing. Postmodern digitalization rends are changing the approach to doing business. Еnterprises are actively implementing business management systems, using telephony and messengers, accounting systems and other applications that are transforming businesses.In the process of enterprise modernization, information becomes a new factor of production, which gradually replaces other factors of production. Тechnology continues to be the largest sector in terms of market capitalization. Effective implementation of innovations, digitalization of business processes allows companies to increase their productivity, achieve the required level of competitiveness and take a stable position in the markets.
Keywords: globalization, innovations, digital technologies, post-industrial society, competitiveness of enterprises, business processes; globalization, innovations, digital technologies, post-industrial society, competitiveness of enterprises, business processes